Análisis de riesgos informáticos y desarrollo de un plan de seguridad de la información para el gobierno autónomo descentralizado municipal de Catamayo. - Calderón Ramos, Viviana Patricia (2016)
The designed plan of information security for Decentralized Autonomous Municipal Government of Catamayo, was developed based on the planning stage of ISO 27001, and the recommendations provided in ISO 27002. The starting point were considered for the design was to identify assets that contribute to the delivery of services to the users addition to the security measures implemented in the institution, finally a risk analysis was conducted, identifying critical assets, as well as the threats to which this exposed such assets and creating risk profiles for each critical asset including impact, likelihood of threat and plan for risk treatment. Based on the study, the safety plan for the institution developed, including policies to be followed by personal and solve technical equipment according to the institution to help ensure the security of information. Implementation and validation of technical solutions that consist of a new logical network design based on VLANS, DHCP was performed, and ACL, optimizing resources that exist in the institution and giving a Guarantee of the information security for validation test plan implementation reply request or echo or gathering information from end users were performed, allowing determine that meet access rules implemented